PENGARUH KONSENTRASI EKSTRAK BAWANG MERAH (Allium cepa L.) TERHADAP PERTUMBUHAN STEK BATANG MAWAR HOLLAND (Rosa hybrida L.) SEBAGAI RANCANGAN HANDOUT BIOLOGI SMA - Fariani, Rafita; Fauziah, Yuslim; L, Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The use of growth regulators in one way to accelerate plant growth and develoment. Growth regulators that are naturally present in plants are auxin, geberelin, cytikinin, abscisic acid, and ethylene. Auxin hormone is a hormone that regulates root growth in plants, can be produced by plants or added from outside (exogenous hormone). This reseach was conducted to determine the concentration of natural growth regulators onion extract which can show the best concentration of root growth and shoots on stem cutting as a design for high school biological handout teaching materials. This reseach used an experimen method with a complete randomized design (RAL) consisting of 6 treatments and 4replications, so that a total of 24 treatments were obtained. The parameters observeb in this reseach incleded the percentage of live cuttings, age of shoots, number of shoots, shoot length, and primary root length. Based on the analysis of variance (ANAVA) at the level 5%, the administartion of shallot extract significantly affected each treatment and it wasfound that concentration of 80% was the best teratment for the parameter age of shoots, number of shoots, shoot length, and primary root length.Kata Kunci: Growth Regulator, Shallot (Allium cepa L.), Auxin, Rose Plant.